Ensino, Aprendizagem e Prática Avaliativa dos Professores de Matematica, do Ensino Médio, em Escolas de Fortaleza. - Sobral, Adriana Eufrásio Braga (2006)
This study has as its objective the evaluation the teaching, learning and assessment practices of mathematic teachers at Intermediate Level Schools in the city of Fortaleza. To attain this object the methodological perspective of MORIN was used. Morin insists that method is a route to be followed as the research develops. The sample was technically arrives at and it determined that 15 public schools and 10 private ones be used in the research from a universe of 282 schools. However, the study in fact covered 13 private schools and 17 public schools. Fifty seven mathematics teachers, currently teaching, were interviewed. The data was collected through interviews containing 14 closed questions and one open one. In each closed question the person being interviewed initially answered as follows on the scale: I agree, I agree in part, I disagree. This was followed by justifying his choice or opinion in more precise detail. All interviews were fully recorded on a tape recorder. Afterwards these recordings were transcribed and edited by the text editor Word for Windows. An analysis of the data was carried out in two stages: a description of the answers by means of Descriptive Statistics, using the program Statistical Package of Social Science (SPSS) and the elaboration into categories using the phenomenological method of reduction of Husserl. The final categories – traditional practice of teaching, renewed vision of teaching, deficient teaching, emphasis in the work of the teacher, - directed the analysis being carried out to characterize the conception of mathematic teachers at Intermediate Level regarding teaching, learning and academic assessment. The results showed that the teachers have consolidated ideas concerning their professional practice that when internalized need to be put into operation in practice. A considerable part of the teachers ideas are in accordance wit the legal determinations expresses in National Curriculum Parameters for Intermediate Teaching.